2017
DOI: 10.1097/mop.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention for preventing food allergy in children

Abstract: Earlier introduction of allergenic foods is a promising intervention to reduce the risk of some food allergies in high-risk infants. Further work is needed to improve knowledge of how to prevent food allergy in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…28,29 However, these studies did not capture information on place of birth, which we found to be important in determining risk of food-induced anaphylaxis in the Asian population. 30 12,13 In our study, children with Asian ancestry more often reported risk of anaphylaxis triggered by soy, wheat and seafood regardless of where they were born.…”
Section: The Association Between Demographic Factors and Anaphylaximentioning
confidence: 51%
See 1 more Smart Citation
“…28,29 However, these studies did not capture information on place of birth, which we found to be important in determining risk of food-induced anaphylaxis in the Asian population. 30 12,13 In our study, children with Asian ancestry more often reported risk of anaphylaxis triggered by soy, wheat and seafood regardless of where they were born.…”
Section: The Association Between Demographic Factors and Anaphylaximentioning
confidence: 51%
“…Reasons for this higher prevalence of anaphylaxis risk to soy, wheat and seafood require further study, but may reflect differences in dietary patterns in the Asian population, including potentially differences in timing of introduction of these foods into the infant diet. 30…”
Section: The Association Between Demographic Factors and Anaphylaximentioning
confidence: 99%
“…Children may be sensitised in utero or while breastfeeding, and as such, maternal diet during pregnancy and breastfeeding has become an increasing focus for food allergy prevention. 72 , 73 As such, key factors which should be included in guidelines, in relation to food allergy prevention, include maternal diet during pregnancy and breastfeeding; timeframe for exclusive breastfeeding; breastmilk substitutes; timing of introduction of solid foods; and recommendations regarding common food allergen introduction. 21 , 74 Other interventions such as vitamin D and omega 3- fatty acid supplementation and modification of the maternal and infant microbiome, remain more controversial 20 and were considered beyond the scope of this review.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there are questions about when to include allergens effectively and safely in the diet, strategies for early consumption versus avoidance of common food allergens are considered a promising intervention to reduce the risk of food allergies. In the general population, more studies are needed to improve information about how to prevent food allergy [11].…”
Section: Food Allergy Preventionmentioning
confidence: 99%